A Case Report of Cake Frosting as a Source of Copper Toxicity in a Pediatric Patient - Tsao, Hoi See (Clin Pract Cases Emerg Med, 2020)
INTRODUCTION: Copper is an uncommon source of metal toxicity in children that requires a high index of suspicion for diagnosis. CASE REPORT: We describe the unique presentation of a 12-month-old girl who developed acute onset of vomiting and diarrhea after ingestion of a copper-contaminated birthday cake. CONCLUSION: This case highlights the presentation, evaluation, and management of the rare pediatric patient who presents with copper poisoning. This case also illuminates the public health implications of potential metal poisoning when using non-edible decorative products in homemade and commercially prepared baked goods.